Complexo cis-[Ru(bpy)2(1,4-dt)L](PF6)X, L=NO ou Cl-: síntese, caracterização, formação de monocamada sobre ouro e potencial aplicação em liberação controlada de óxido nítrico - Ferreira, Millena Pereira (2017)
Resumo em Inglês: In this work, the cis-[Ru(bpy)2(Cl)(1,4-dt)]PF6 complex where 1,4-dt = 1,4-dithiane and bpy = 2,2-bipyridine, was synthesized and characterized by means of vibrational spectroscopic techniques, electronic and electrochemical measurements. The results indicated that the cis- [Ru(bpy)2(Cl)1,4-dt]+ complex was synthesized with a satisfactory degree of purity and that the 1,4-dt linker confers greater stability to the reduced state metal center due to the π-backbonding effect, compared to the cis-[Ru(bpy)2(Cl)2] precursor complex. 1H and 13C NMR spectra suggest that the 1,4-dt is coordinated by only one sulfur atom and there is only one 1,4-dt ligand in the ion sphere of the metal. The 1,4-dt ligand allowed this complex to adsorb on gold substrates. Aiming to verify the monolayer formation of the complex, studies using Surface Enhanced Raman Scattering (SERS) and electrochemical impedance techniques were carried out. The results indicated that the cis-[Ru(bpy)2(Cl)(1,4-dt)]+ complex ion adsorbs spontaneously on the gold surface, forming the monolayer complex, through the sulfur atom of the 1,4-dt. Additionally, surface saturation is reached after ca. 60 min. The SERS results confirm the proposed structure for the cis-[Ru(bpy)2(Cl)(1,4-dt)]+ complex adsorbed on gold. The interaction study of the monolayer Au/[Ru(bpy)2(Cl)(1,4-dt)]+ with NO by electrochemical cyclic voltammetry technique did not present NO coordination responses. Thus, the synthesis and characterization of the cis-[Ru(bpy)2(1,4-dt)NO](PF6)3 complex, as well as the formation of monolayer Au/[Ru(bpy)2(1,4- dt) NO]3+ and the NO release studies by the SECM technique indicate that NO molecule is released from the surface of potential application.